EFEKTIVITAS SUPERVISI KEPALA RUANGAN MENGENAI KEPATUHAN PERAWAT DALAM MENERAPKAN FALL RISK ASESSMENT PADA PASIEN RAWAT INAP DI RUANG CENDANA II RUMAH SAKIT BHAYANGKARA TK.I R. SAID SUKANTO - Nurhidayah Perwaningsih (2022)
The risk of falling is a condition where the patient is at risk of injury and serious injury due to falls while being treated in hospital. Fall risk assessment is an effort to prevent the risk of falling in patients that must be carried out by nurses and filled out accurately according to the patient's condition. Non-compliance in implementing the Fall Risk Assessment is a problem which can bring harm to nurses, agencies and especially to patients. The results of observations made by the author in the Cendana II Room at Bhayangkara Tk.I R. Said Sukanto Hospital showed that from 5 nurses, 4 people (80%) showed disobedience in applying the Fall Risk Assessment to inpatients while 1 person (20%) show obedience. Based on these results, the authors conducted evidence based nursing in the form of health education and observations of the implementation of supervision carried out by the Head of the Room for 5 nurses who were the targets of the intervention. The intervention lasted for three days in a row with pre-test and post-test for nurses. The results of the post test evaluation after the five nurses were supervised by the Head of the Room showed that as many as 5 people (100%) had shown an obedient attitude in applying the Fall Risk Assessment to inpatients. This shows that the supervision of the Head of the Room is proven to be helpful in improving the performance of nurses and the quality of health services.